Ketergantungan Penggunaan Aplikasi AI dalam Keefektivitasan Belajar pada Mahasiswa Manajemen Pendidikan Islam - Ummu Hanifah; Novebri Novebri (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This research aims to measure the influence of dependence on the use of artificial intelligence (AI) applications on the learning effectiveness of Islamic Education Management students. Using quantitative research methods, data was collected through questionnaires distributed to 150 students at several universities. Data analysis was carried out using a simple linear regression test to determine the correlation between the dependency variable on AI applications (X) and learning effectiveness (Y). The research results show that 78% of respondents use AI applications in their daily learning activities, with 65% of them feeling more efficient in accessing information. However, there are 40% of students who show decreased motivation for independent learning due to dependence on AI applications. The results of the regression test show that there is a significant positive correlation between the use of AI applications and learning effectiveness with a correlation coefficient of 0.52 and a significance of p < 0.05. These findings indicate that the use of AI plays an important role in increasing learning effectiveness, but also has the potential to reduce motivation for independent learning. It is hoped that the use of AI will be accompanied by learning strategies that support student independence and critical thinking.